2017
DOI: 10.1186/s13059-017-1201-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple gene movements into and out of haploid sex chromosomes

Abstract: BackgroundLong-term evolution of sex chromosomes is a dynamic process shaped by gene gain and gene loss. Sex chromosome gene traffic has been studied in XY and ZW systems but no detailed analyses have been carried out for haploid phase UV sex chromosomes. Here, we explore sex-specific sequences of seven brown algal species to understand the dynamics of the sex-determining region (SDR) gene content across 100 million years of evolution.ResultsA core set of sex-linked genes is conserved across all the species in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
139
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(158 citation statements)
references
References 64 publications
19
139
0
Order By: Relevance
“…This result was consistent with the findings in the conservative analysis of SDR genes among brown algae by Lipinska et al. (). The prediction of protein domains revealed that SjHMG has two typical HMG‐box domains.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result was consistent with the findings in the conservative analysis of SDR genes among brown algae by Lipinska et al. (). The prediction of protein domains revealed that SjHMG has two typical HMG‐box domains.…”
Section: Discussionsupporting
confidence: 93%
“…( Ec‐13_001750 ), which implied that it was a candidate sex‐determining gene (Lipinska et al. ). In this study, the male‐specific SjHMG gene was found to be orthologous to the male SDR gene Ec‐13_001750 of Ectocarpus , which was conservative among other brown algae with the UV sex determination system (Lipinska et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Partial sequences of the sex‐specific non‐recombining regions in the female and male sex‐determining regions (Lipinska et al. ) were amplified and used as the sex markers (Hoshino et al. 2018b).…”
Section: Methodsmentioning
confidence: 99%